The role of the perceived environment for recreational walking among adults in socioeconomically disadvantaged situations: A study using walk-along interviews - Suzannah D'Hooghe; Yasemin Inaç; Benedicte Deforche; Delfien Van Dyck; Karin de Ridder; Stefanie Vandevijvere; Nico Van de Weghe; Sarah Dury (Elsevier, 2023)
Background: Persons in socioeconomically disadvantaged situations (PSEDS) are generally less likely to engage in recreational walking (RW) compared to higher socioeconomic groups and are often more dependent on their local environment. Studies on RW have primarily focused on the role of the built environment for the general adult population and the older population in urban areas. The aim of this study is to qualitatively identify the perceived environmental factors affecting RW among PSEDS in peri-urban areas. Methods: In two peri-urban municipalities in Belgium, walk-along interviews were conducted until data saturation with a purposeful convenience sampling of 38 PSEDS (25-65y/o) to identify local environmental factors affecting RW. A subsample of 22 participants joined a focus group (n = 4) to categorize the identified factors into environmental types (physical, sociocultural, political, and economic) of the Analysis Grid for Environments Linked to Obesity (ANGELO) framework. The interviews were transcribed and analyzed thematically using Maxqda 2022.0. Results: The information environment (dissemination, retrieving and understanding of information) was added to the ANGELO framework, highlighting the importance of digital literacy. Availability and accessibility of well-maintained walking surfaces, toilets, street lighting and seating options (physical environment), social support, dog-ownership, stigmatization, social isolation, and a sense of belonging (sociocultural environment) and indirect costs (economic environment) were identified as important environmental factors in RW among PSEDS. The identified political and economic factors are intertwined with the other environments. Conclusions: Perceived environmental factors affect RW among PSEDS and peri-urban settings offer specific challenges. Local governments should incorporate citizen perception into decision-making processes to create supportive environments that have the potential to promote RW among PSEDS in a peri-urban setting.